Experimental search for long-range forces in neutron scattering via a gravitational spectrometer - Serebrov, Anatoli P.; Geltenbort, Peter; Zherebtsov, O. M.; Sbitnev, S. V.; Varlamov, V. E.; Vassiljev, A. V.; Lasakov, M. S.; Krasnoschekova, I. A.; Ivanov, S. N.; Pushin, Dimitry A. (American Physical Society, 2014)
In this work we introduce a method of measuring low-energy scattering cross section with a gravitational spectrometer. In this method we add atoms (i.e., He) to the gravitational spectrometer filled with a target gas of ultracold neutrons (UCN). We search for long-range forces between atoms and UCN by measuring transfer of a small recoil energy similar to 10(-7) eV using the gravitational spectrometer. As a result of this search we set new constraints on the strength of long-range forces within the range of the effective radius of interaction of 10(-7)-10(-4) cm.
© 2014 American Physical Society, https://dx.doi.org/10.1103/physrevc.89.044002
Keywords: inverse-square law; extra dimensions; cross-sections; gases; tests